DEVELOPMENT OF MANAGERIAL COMPETENCE OF PUBLIC-PRIVATE PARTNERSHIPS IN THE FIELD OF VOCATIONAL EDUCATION AND TRAINING (Innovative professional education, 2024)
The results of the experiment «Development of managerial competence of subjects of public-private partnership in the field of vocational (vocational-technical) education» on the topic of the scientific research «Trends in the development of public-private partnership in the field of vocational (vocational-technical) education» of the Institute of Vocational Education of the NAES of Ukraine (2022–2024) are characterized. The purpose, objectives, hypothesis, experimental base, research methods are specified, the main stages of experimental work are described. According to the results of the ascertaining stage of the study, it was determined that Ukraine lacks a single algorithm for the regulatory and legal regulation of public-private partnership in the field of vocational education; the involvement of business and public representatives in the work of vocational education institutions is low; the process of assessing the heads of institutions of their managerial skills is procedurally unsecured; the introduction of modules and programs for the development of managerial competence of managers and teachers, the content of which includes technologies for the development of public-private partnership in the field of vocational education, is becoming relevant. During the formative stage of the experiment, the effectiveness of technologies for the development of public-private partnership in the field of vocational (vocational and technical) education was tested by means of educational and methodological support for their implementation, conducting a series of scientific and practical events, and training managers and teachers of vocational (vocational and technical) education institutions under the advanced training program. At the generalization stage, the results of the experiment were analyzed, which showed an increase in the level of development of managerial competence of managers and teaching staff of vocational educationinstitutions and confirmed the hypothesis regarding the effectiveness of the proposed technologies.
Keywords: subjects of public-private partnership, managerial competence, professional (vocational) education, experiment